Nepal Economic Update, April 2014 - World Bank (Washington, DC, 2014)
The enabling environment for the development of Nepal has improved, but opportunities need to be effectively leveraged through focused policy action. Nepal has significant resources in the form of remittances from abroad, but the economy cannot use these resources in a productive manner to enhance the overall welfare of all citizens. Specific priorities for development include: (1) creating a growth promotion vision and agenda; (2) resolution of Nepal's "fiscal paradox"; (3) boosting investments; and (4) tackling enduring financial sector risks and managing excess. After a difficult year in FY13, the economy is poised to recover, albeit modestly. In FY13, Nepal achieved only modest growth of 3.6 percent. This was due largely to poor performance of the agricultural sector as well as very modest levels of industrial activity. Nepal s internal and external balances are sound but not for the right reasons. Low expenditure and robust revenue growth accounted for a large budget surplus and declining debt. Nepal s external position is comfortable because of large remittance inflows. On the external side, Nepal has benefited from the depreciation of the rupee but also - and much more significantly - from a sharp further increase in inward remittances which are expected to amount to over 30 percent of GDP in FY14. Monetary policy has sought to achieve a delicate equilibrium between controlling inflation and supporting economic activity but the optimal balance may evolve and call for corrections. For FY14, the outlook is cautiously optimistic. As remittances have become a defining feature of the Nepali economy the country must learn to manage excess liquidity.